Biochemical, biophysical, and functional characterisation of the E3 ubiquitin ligase APC/C regulator CDC20 from Arabidopsis thaliana - Cosma, Maria-Alexa; Curtis, Natalie L.; Pain, Charlotte; Kriechbaumer, Verena; Bolanos-Garcia, Victor M. (Frontiers in Physiology, 2022)
The Anaphase Promoting Complex (APC/C), a large cullin-RING E3-type ubiquitin ligase, constitutes the ultimate target of the Spindle Assembly Checkpoint (SAC), an intricate regulatory circuit that ensures the high fidelity of chromosome segregation in eukaryotic organisms by delaying the onset of anaphase until each chromosome is properly bi-oriented on the mitotic spindle. Cell-division cycle protein 20 homologue (CDC20) is a key regulator of APC/C function in mitosis. The formation of the APC/CCDC20 complex is required for the ubiquitination and degradation of select substrates, which is necessary to maintain the mitotic state. In contrast to the roles of CDC20 in animal species, little is known about CDC20 roles in the regulation of chromosome segregation in plants. Here we address this gap in knowledge and report the expression in insect cells; the biochemical and biophysical characterisation of Arabidopsis thaliana (AtCDC20) WD40 domain; and the nuclear and cytoplasmic distribution of full-length AtCDC20 when transiently expressed in tobacco plants. We also show that most AtCDC20 degrons share a high sequence similarity to other eukaryotes, arguing in favour of conserved degron functions in AtCDC20. However, important exceptions were noted such as the lack of a canonical MAD1 binding motif; a fully conserved RRY-box in all six AtCDC20 isoforms instead of a CRY-box motif, and low conservation of key residues known to be phosphorylated by BUB1 and PLK1 in other species to ensure a robust SAC response. Taken together, our studies provide insights into AtCDC20 structure and function and the evolution of SAC signalling in plants.